Understanding mixtures: Chemistry workshop-2 - Seymour Rosen (Globe Book, 1977)
This book discusses liquid solution, freezing and boiling of water. It presents reaction of mixture of an acid with a base, porvides also the kinds of liquids and some solutions that conduct electricity. There are exercises at the end of each lesson